Impact of strategy conformity on vaccination behaviors - An, Tianbo; Wang, Jingrui; Zhou, Bowen; Jin, Xing; Zhao, Jian; Cui, Guanghai (Frontiers in Physics, 2022)
In most of studies focusing on the conformity of voluntary vaccination decisions, the conformity was always directly modeled as conformity-driven strategy updating rule. However, the utility of an individual can also be influenced by the group identity or discrimination behaviors associated with strategy conformity in realities. Thus, a novel utility model of vaccination game is firstly formulated in which the influence of strategy conformity is considered. Then, we use spatial evolutionary game theory to study the dynamics of individual vaccination strategies under the influence of strategy conformity in the scale-free network. The results show that moderate strategy conformity and high herd immunity threshold have a significant positive effect on vaccination behaviors when the initial vaccination fraction is low. Moreover, for high initial vaccination fraction, the strong strategy conformity and high herd immunity threshold are more conductive to encourage vaccination behavior. To analyze the model sensitivity, experiments are conducted in the small world network and square lattice network. In addition, we provide the sensitivity analysis on vaccination effectiveness. Finally, the generality of strategy conformity effect is investigated when the myopic strategy updating rule is adopted in the whole population. The result shows vaccination behaviors can also be promoted under the condition of moderate strategy conformity and low initial vaccination fraction.